Natural Polyphenols as Targeted Modulators in Colon Cancer: Molecular Mechanisms and Applications - Long, Jing; Guan, Peng; Hu, Xian; Yang, Lingyuan; He, Liuqin; Lin, Qinlu; Luo, Feijun; Li, Jianzhong; He, Xingguo; Du, Zhiliang; Li, Tiejun (Frontiers in Immunology, 2021)
Colon cancer commonly develops from long-term chronic inflammation in the intestine and seriously threatens human health. Natural polyphenols have been valued as a crucial regulator of nutrient metabolism and metabolic diseases, owing to their anti-inflammatory and antioxidant functions and the ability to maintain a balance between gut microbes and their hosts. Notably, many experimental and clinical evidence has shown that natural polyphenols could act as a targeted modulator to play a key role in the prevention or treatment of colon cancer. Thus, in this review, we summarized recent advances in the possible regulatory mechanism and the potential application of natural polyphenols in colon cancer, which might be regarded as a novel platform for the colon cancer management.